Differentials in Ever Use of Contraceptive Methods among the Danuwar Community of Lalitpur, Nepal - Devkota, Bijaya Mani; Bohara , Pradeep Kumar (Educational Journal, 2025)
Nepal is yet to experience much disparity between the indigenous people of Nepal, which is even although national development is shifting to family planning. The primary research is to identify the demographic and socio-economic factors with respect to the ever-use of the contraception method. This research demonstrates the differences in the use of contraceptive methods in the ever-use amongst Danuwar women of Godawari Municipality-8 (Dukuchap), Lalitpur. A cross-sectional survey of 289 women carried out in 2025 was conducted to assess the relationship between the use of contraception in the past and the variables, including age, education, employment, knowledge, son preference, income, migration, and intentions to have children. 78.3 percent of the women had ever used contraception. The use of contraceptives rose with age (58.8% 15-24 years, 76.3% in 25-34 years, and 85.3% in 35-49 years; chi2=5.92; p=0.052). Knowledge of modern methods had a very high association with the use (83.8% vs. 15.4; 2=32.86; p 0.001). Son preference (χ 2 =9.06, p=0.003), perceived government policy support (χ 2=7.60, p 0.006), and fertility intentions (2=6.89, p=0.009) were significantly predicted. The impact of income was nearly strong. The study is important to the current body of knowledge in that the author offers community-level evidence that, despite an effect of socio-economic status on contraceptive use, awareness, gender norms, fertility intentions, and policy support are dominant influences in influencing contraceptive use among an understudied indigenous population in Nepal. The use of contraception mostly depends on awareness, age, gender norms, fertility intentions, and even support through policies. Culturally sensitive gender-responsive interventions are needed to aid in the realization of FP 2030 and SDG 3.7 goals in marginalized communities.